Diagnostic accuracy of pH monitoring in gastro-oesophageal reflux. Issue 10 (October 1989) - Da Dalt, L; Mazzoleni, S; Montini, G; Donzelli, F; Zacchello, F
Abstract : One hundred and eleven children admitted with suspected gastro-oesophageal reflux were studied, with 24 hour oesophageal pH monitoring as the first line of investigation. Barium swallow examination, or oesophagoscopy, or both, were carried out only in children with abnormal pH, who subsequently had a trial of 1-12 months medical treatment. All patients were followed up for eight months to two years. A final diagnosis of gastro-oesophageal reflux was made in 41 patients, in all of whom the pH study was abnormal (100% sensitivity). The final diagnosis was different in 70 patients; 66 of these had a normal pH (94% specificity). All children with gastro-oesophageal reflux were treated with drugs. All those with a percentage reflux time of more than 27 and more than 20 episodes of reflux lasting more than 5 minutes failed to improve and needed operation. We conclude that monitoring of the oesophageal pH should be the first line of investigation in patients with gastro-oesophageal reflux and should be used together with clinical data and other investigations, to identify those children who will need operation.